MODERN ASPECTS OF THE APPLICATION OF LOCAL ANESTHESIA IN THE PRACTICE OF VETERINARY MEDICINE - Sliusarenko, Dmytro; Tsimerman, Olesya; Syniahovska, Kateryna; Sarbash, Dmytro; Khokhlova, Uliana (European Science, 2023)
Local anesthesia provides long-term, safe loss of sensitivity of a certain part of the animal's body with a minimum number of side effects. It is also able to selectively provide analgesia and muscle relaxation without suppressing the functions of the cen